Patient Awareness of Cost of Treatment at a Government Sponsored Hospital in India - Ritesh, .; Singh, Harsh Mohinder; Singh, Bikram Jit (Journal of Nepal Paediatric Society, 2019)
Introduction: To evaluate the awareness amongst the beneficiary about the costs of medical services in a hospital which provides all services at no cost and also to analyse whether education level of the beneficiary client, number of days stayed in hospital and their prior exposure of being treated on payment in other hospital has some bearing on cost estimation by the participants. Method: It was a cross sectional questionnaire based survey study. A total of 130 beneficiary clientele of a government hospital were interviewed. Two sample ‘t’ test and ANOVA were used for statistical analysis. Multivariate regression analysis was used to study effect of more than one independent variable on cost estimation. Scatter plot and box plots were used to study standard deviation. Results: It revealed poor awareness of people in cost estimation of medical expenses. A significant ‘p’ value of < 0.05 was observed with respect to length of stay (p = 0.003), treatment modality (p = 0.000) and multivariate variable (treatment technique along with exposure to treatment in paid hospital, p = 0.008). Conclusion: The beneficiary clientele in a hospital with free treatment generally not aware about the exuberant costs of treatment born by the state.